Weathering the Storm: Sverre Petterssen, the D-Day Forecast, and the Rise of Modern Meteorology - Petterssen, Sverre (American Meteorological Society, 2001)
This book presents the memoirs of Sverre Pettersen, prominent leader in the field of meteorology. Delving through his recollections of hischildhood in Norway, education and work at the famous Bergen school of Meteorologyto the World War II crisis and D-Day, Petterssen uncovers the history of meteorology, documenting it from his perspective. Meteorology today is the beneficiary of his work